The PENERAPAN HUKUM ADAT DALAM PEMBERIAN SANKSI BAGI PELAKU PENCURIAN MENURUT SUKU DAYAK TAMAN SOSAT (Faculty of Law, University of Palembang, 2024)
Crimes of theft still often occur around the community, both in cities and villages. Solving crimes of theft in villages more often uses customary law as the first route in resolving these problems. The Indonesian state recognizes the existence of Customary Law and respects traditional rights that develop among indigenous communities. This research aims to discuss the application of Customary Law in imposing sanctions in the form of Customary Sanctions, especially for the Taman Sosat Dayak Tribe with the research location in Sungai Lawak Village, Nanga Taman District, Sekadau Regency, West Kalimantan Province. This research uses empirical research with a qualitative approach with data collection techniques in the form of direct observation, interviews with parties determined as the population and samples to obtain primary data in the research. The results of this research explain that the application of Customary Law in resolving acts of theft against the Dayak people of Taman Sosat is through the provision of EnomBalas Customary Sanctions or the Sixteen Poku Customs. This customary sanction is one of the sanctions in the Taman Sosat Dayak tribe's customary law which has been preserved from the time of their ancestors. These traditional sanctions can be carried out in each hamlet led by the traditional leader and the parties involved in the theft. In giving sanctions, several supporting equipment is required, such as using chicken blood, palm wine, and traditional bowls. The role of the Dayak Taman Sosat tribal community in preventing theft in Sungai Lawak Village is very important.